2014
DOI: 10.1186/2053-8871-1-4
|View full text |Cite
|
Sign up to set email alerts
|

From mice to men: lessons from mutant ataxic mice

Abstract: Ataxic mutant mice can be used to represent models of cerebellar degenerative disorders. They serve for investigation of cerebellar function, pathogenesis of degenerative processes as well as of therapeutic approaches. Lurcher, Hot-foot, Purkinje cell degeneration, Nervous, Staggerer, Weaver, Reeler, and Scrambler mouse models and mouse models of SCA1, SCA2, SCA3, SCA6, SCA7, SCA23, DRPLA, Niemann-Pick disease and Friedreich ataxia are reviewed with special regard to cerebellar pathology, pathogenesis, functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 322 publications
(423 reference statements)
2
74
0
Order By: Relevance
“…They attracted the attention of the investigators not only as possible models of human ataxias (Cendelin, 2014), but also as invaluable tools to study the normal cerebellar development in times when genetic engineering was still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They attracted the attention of the investigators not only as possible models of human ataxias (Cendelin, 2014), but also as invaluable tools to study the normal cerebellar development in times when genetic engineering was still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence supports the hypothesis that an absence of Reelin causes a loss of the CGCs and the PNs in the cerebellar cortex (Cendelin, 2014), very limited information is available on the occurrence and type of postnatal cell death in mutants. Our group has demonstrated that the CGCs of the Reeler mouse undergo apoptosis after TUNEL labeling of fragmented DNA, and that apoptosis in mutants is significantly higher than in normal wild-type (WT) littermates (Cocito et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous nature of the cerebellar ataxias combined with the unavailability of human brain tissue and the lack of reliable disease models have, however, hampered our understanding of the molecular disease mechanisms underlying cerebellar ataxias and thus, the development of effective therapies. Although mouse models of several cerebellar ataxias, including FRDA and SCAs, have provided valuable insights into the pathophysiology of these disorders (reviewed in 9 ), many questions remain about the observed species differences in disease phenotypes and the effectiveness of potential drugs in clinical trials. To help translate research from animal models into novel treatments for ataxia patients, it is essential to validate findings in the relevant affected human cell types, particularly in cerebellar Purkinje cells.…”
Section: Cerebellar Ataxiasmentioning
confidence: 99%
“…The weaver homozygotes have been studied as an animal model of cerebellar disorders such as hereditary ataxias (Grüsser-Cornehls and Bäule 2001, Manto and Marmolino 2009, Cedelin 2014. GIRK2 is expressed, in the weaver cerebellum, from embryonic day 15 to postnatal day 20 (Wei et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebellar disorders such as ataxias are severe neurological conditions that comprise a wide spectrum of diseases characterized by motor incoordination, imbalance and degeneration of PCs (Grüsser-Cornehls and Bäule 2001, Manto and Marmolino 2009, Cedelin 2014). …”
Section: Introductionmentioning
confidence: 99%